2014
DOI: 10.1063/1.4874272
|View full text |Cite
|
Sign up to set email alerts
|

Large enhancement of ferromagnetism by Cr doping in Mn3O4 nanowires

Abstract: The Mn3O4 nanostructures having low temperature Curie point (45 K) disqualify them for most practical applications. In this work, single-crystalline Cr-doped Mn3O4 nanowires with ferromagnetic Curie point at room temperature (305 K) have been investigated. Our experimental results show an increase in effective magnetic moment per gram as Cr3+ replaces Mn3+ and oxygen vacancies, which result in a transition from paramagnetic (Mn3O4) to ferromagnetic. The doped Cr3+ and oxygen vacancies reveal the remarkable fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…For all doped samples, we also see the rise of the background due to the Compton phenomenon 28 enhanced by increasing the content of zirconium or samarium ion in initial as-synthesis gel. Moreover, it is clear that the intensity of peaks decreases sharply as the concentration of dopant (Zr or Sm) increases, providing evidence that the dopant (Zr or Sm) is forming defects during doping that leads to promoting amorphization and segregation of the dopant (Zr or Sm) which promote the growth of the particle size 23,25,29,30 . This finding is confirmed by the calculation of average crystallite size via Debye Scherer formula 31 According to the X-ray diffraction pattern achieved for a synthetic sample of zeolite 4A using clinoptilolite and sodium aluminate and comparison with the reference pattern (01-071-1571), crystallization in cubic system with Pm-3m space group as long as the chemical formula of Na12A12Si12O48 is confirmed for the prepared zeolite 4A.…”
Section: Photocatalytic Studiesmentioning
confidence: 99%
“…For all doped samples, we also see the rise of the background due to the Compton phenomenon 28 enhanced by increasing the content of zirconium or samarium ion in initial as-synthesis gel. Moreover, it is clear that the intensity of peaks decreases sharply as the concentration of dopant (Zr or Sm) increases, providing evidence that the dopant (Zr or Sm) is forming defects during doping that leads to promoting amorphization and segregation of the dopant (Zr or Sm) which promote the growth of the particle size 23,25,29,30 . This finding is confirmed by the calculation of average crystallite size via Debye Scherer formula 31 According to the X-ray diffraction pattern achieved for a synthetic sample of zeolite 4A using clinoptilolite and sodium aluminate and comparison with the reference pattern (01-071-1571), crystallization in cubic system with Pm-3m space group as long as the chemical formula of Na12A12Si12O48 is confirmed for the prepared zeolite 4A.…”
Section: Photocatalytic Studiesmentioning
confidence: 99%
“…As no peak shi is observed (Fig. S1 [45][46][47] Herein, doping is possible due to the comparable ionic radius of Mn 2+ (0.80 Å) and Ni 2+ (0.69 Å). 46,47 where k is the shape factor ($0.9), l is the X-ray wavelength (1.5406 Å), b is the full width at half maximum (FWHM) of the corresponding diffraction line and q is the diffraction angle.…”
Section: Structure Morphology and Compositionmentioning
confidence: 99%
“…These results support the crystallinity of the as prepared sample and are in good agreement with recent literature. 45,49 To support the XRD and TEM results, we have investigated the distribution of replaced/doped Ni as Ni 2+ in the Mn 2+ lattice in the Mn 3 O 4 sample through energy dispersive X-ray uorescence (XRF) and energy-dispersive spectroscopic (EDS) elemental mapping. This journal is © The Royal Society of Chemistry 2016…”
Section: Structure Morphology and Compositionmentioning
confidence: 99%
“…Furthermore, Zhao et al synthesized Sn-doped Mn3O4/C nanocomposites for supercapacitor electrode with higher capacitance [12]. Moreover, Li et al [13] showed that Cr doping could enhance ferromagnetic properties of Mn3O4 nanowires. This material is a good candidate for photodegradation of organic dyes, since ferromagnetic materials such as Fe3O4 are confirmed as good photocatalysts.…”
Section: Introductionmentioning
confidence: 99%